Новые разработки для предотвращения образования холодных трещин в сварных соединениях мартенситных теплоустойчивых сталей - Мейир, П.; Серьяк, Х. (Автоматическая сварка, 2008)
HAZ of a new steel grade of the system 9Cr–3W–3Co–V–Nb with controlled adding of boron and nitrogen was investigated using physical simulation of a weld. After the complete thermal cycle of welding the size of grains of primary austenite and structure of lath martensite are identical to those in initial state. The suppression of fine-grained HAZ formation shows high potential of a new steel as for the reduce of tendency of joints towards cold cracks formation.